Preliminary pharmacological screening of Corchorus olitorius extracts for anti-inflammatory and wound healing activity (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Aim of present study was to investigate the preliminary screening of aerial part of Corchorus olitorius extracts for anti-inflammatory and wound-healing activity on experimental animals. Different extracts with respective solvents i.e. petroleum ether, chloroform, ethyl acetate, ethanol and aqueous extracts of C. olitorius were obtained by successive solvent extraction. All extracts were screened for anti-inflammatory activity using Xylene-induced ear edema in mice and wound healing effect was studied by using incision wound model in mice. The weight of the ear lobes and biochemical measurements, nitric oxide (NO) levels and MPO in the tissue sample were used to detect the anti-inflammatory effect. The wound healing effect was observed by measurement of tensile strength and protein and hydroxyproline level assessment in the healed tissues. Observations of present study were confirmed that ethanol extract of C. olitorius (EECO) was showed significant (p<0.05) inhibition in the ear edema of mice. NO and MPO activity was decreased significantly in EECO-treated mice. Wound healing potential was observed by significant improvement in tensile strength as well as protein and hydroxyproline level of healed tissue of EECO-treated mice. In conclusion, ethanol extract of C. olitorius was found most effective for anti-inflammatory through reduction of NO and MPO activity as well as wound healing potential in experimental mice.